Prospects for constitutionalism in post-communist countries - Gönenç, Levent (The Hague ; New York : Martinus Nijhoff, 2002)
The main questions dealt with throughout this study can be formulated as follows: Will liberal democratic constitutionalism take root in post-communist countries? And will new constitutions in Eastern Europe and the former USSR perish or survive?
List of Tables; Acknowledgements; Introduction; Chapter 1. Conceptual Framework; Chapter 2. Political Culture; Chapter 3. Constitution-Making; Chapter 4. Effectiveness; Chapter 5. Constitutional Change and Consolidation of Democracy; Bibliography; Index; About the Author.
Includes bibliographical references (pages 383-417) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Constitutional law -- Europe, Eastern; Post-communism -- Former Soviet republics; Democracy; Droit constitutionnel -- Europe de l'Est.; Postcommunisme -- Ex-URSS.; LAW -- Constitutional; LAW -- Public; Constitutional law; Democracy; Post-communism; Eastern Europe; Soviet Union -- Former Soviet republics; Demokratisierung; Verfassung; Politische Kultur; Osteuropa; Constitutionalisme; GUS